2015
DOI: 10.17762/ijritcc2321-8169.150145
|View full text |Cite
|
Sign up to set email alerts
|

Modified RR Algorithm with Dynamic Time Quantum for Externally Prioritized Tasks

Abstract: Abstract-The objective of this paper is to modify Round Robin scheduling for soft real time systems. It introduces a variation of round robin algorithm which can schedule tasks considering their priorities in a round robin fashion. Simple Round Robin scheduling algorithm and Priority scheduling algorithm, both have their own drawbacks. The proposed algorithm removes the drawbacks of Round Robin scheduling and Priority scheduling. The proposed scheduling algorithm calculates different time slices for individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…From the above comparisons, it is observed that the proposed algorithm is performing better than the algorithm PBDRR proposed in paper [7] and DQT proposed in paper [9] in terms of average waiting time, average turnaround time and number of context switches. If the CPU burst times of the processes vary very widely the algorithm doesn't produce good result.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…From the above comparisons, it is observed that the proposed algorithm is performing better than the algorithm PBDRR proposed in paper [7] and DQT proposed in paper [9] in terms of average waiting time, average turnaround time and number of context switches. If the CPU burst times of the processes vary very widely the algorithm doesn't produce good result.…”
Section: Resultsmentioning
confidence: 87%
“…In [8] the authors have made the priority and time slice for a process dynamic by calculating the weighted mean values of time quantum and priorities of the processes and considering the burst time of the processes. The algorithm introduced in [9] calculates the time slice of each process in each round dynamically considering the priority of a process and the average and shortest burst time of all the currently running processes. Fuzzy logic is applied in the design and implementation of a rule-based scheduling algorithm to solve the shortcoming of well-known scheduling algorithms in [10].…”
Section: Related Work Donementioning
confidence: 99%
See 1 more Smart Citation
“…The objective of [3] is to modify Round Robin algorithm by adjusting time slices of different rounds depending on the remaining CPU bursts of currently running processes and coinciding their waiting time until that round in request of the other processes' waiting time. The [4] proposal calculates different time slices for individual processes coinciding their priorities. The primary objective of [5] is to optimize system performance according to the criteria deemed most important by system designers.…”
Section: Related Workmentioning
confidence: 99%
“…Some other process scheduling algorithms include First Come First Serve (FCFS) and Shortest Job First (SJF) algorithms [7], [8]. FCFS algorithm executes the first process that comes in the ready queue and that process is executed fully till its burst time is finished [4], [6], [8]. Shortest Job First (SJF) algorithm executes the process with the minimum burst time first and executes it till its burst time is finished.…”
Section: Introductionmentioning
confidence: 99%